Idea sharing: process-based approach to writing in Malaysian English education - Kee, Li Li; Mohamed Razali, Abu Bakar (2019)
Malaysia strives to educate its people to be fluent in the English language, and as such the Ministry of Education Malaysia (MOE) has introduced the process-based approach to writing from the early 1980s in school curricula and syllabi. Unfortunately, even from the inclusion of process-based approach to writing in Malaysian national curricula and syllabi, Malaysian students' writing performance in the national primary and secondary school examinations remains low. Concerns arise over the process-based approach, due to its lack of proper implementation in the English as a second language (ESL) writing instruction. This article provides a review of the studies conducted on the implementation of process-based approach in teaching ESL writing in Malaysian English education. It seeks to investigate the problems that have been reported to occur during the implementation of process-based approach in the ESL writing instruction in Malaysia. In order to address the concerns regarding process-based approach to writing and to avoid possible issues in the future concerning the implementation of process-based approach in ESL writing in Malaysia, the researchers believe it is important to truly understand the nature and goals of the process-based approach to writing. 318 | PASAA Vol. 58 July-December 2019 as such, the researchers call all educators in Malaysia to look for possible means to revive the process-based approach in the field of ESL writing.